2020
DOI: 10.3390/pathogens9030184
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Helicobacter pylori into Coccoid Forms as a Challenge for Research Determining Activity of Antimicrobial Substances

Abstract: Morphological variability is one of the phenotypic features related to adaptation of microorganisms to stressful environmental conditions and increased tolerance to antimicrobial substances. Helicobacter pylori, a gastric mucosal pathogen, is characterized by a high heterogeneity and an ability to transform from a spiral to a coccoid form. The presence of the coccoid form is associated with the capacity to avoid immune system detection and to promote therapeutic failures. For this reason, it seems that the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 92 publications
2
37
0
2
Order By: Relevance
“…It also bears noting that recent research has found that H. pylori can sometimes transform from the expected spiral form to a coccoid form, which could result in an inaccurate AST if the bacteria are in a viable-but-nonculturable state. This transformation could result in treatment failure without the presence of ARGs, further complicating the picture of AMR in H. pylori [ 39 ]. While WGS may be useful in overcoming the limitations of studies by allowing analysis of the full resistome, the relative contribution of each mutation to the MIC as well as the effect of combinations of mutations and shape transformation remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It also bears noting that recent research has found that H. pylori can sometimes transform from the expected spiral form to a coccoid form, which could result in an inaccurate AST if the bacteria are in a viable-but-nonculturable state. This transformation could result in treatment failure without the presence of ARGs, further complicating the picture of AMR in H. pylori [ 39 ]. While WGS may be useful in overcoming the limitations of studies by allowing analysis of the full resistome, the relative contribution of each mutation to the MIC as well as the effect of combinations of mutations and shape transformation remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of 3-BP and SER has been extended to assess morphological changes in H. pylori , a process for which an involvement in antibiotic tolerance is suggested [ 56 , 57 ]. Bacteria treated with these substances underwent morphological transition to spherical cells ( Figure 3 and Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon seems to be particularly interesting in the case of AMX, because this antibiotic had a very high bactericidal activity against planktonic forms (a microdilution method, MIC = 0.06–0.12 µg/mL) and freshly seeded cells settled on the agar (growth inhibition zones produced by 25 µg/disk being ~60 mm), while significantly lower in relation to 3 day-old, lawn H. pylori biofilms (reduction of CFU/mL after a 4-h incubation was <3 logs). A high level of green fluorescence suggests that the observed decrease in CFU/mL is rather associated with the loss of culturability in the process of transformation into coccoid forms than the reduction of viability [ 57 ]. Our observations are consistent with the reports of others indicating a low bactericidal activity of AMX against biofilm H. pylori forms [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, however, an alarmingly high detection of multidrug-resistant (MDR) H. pylori strains is observed [ 8 ]. Factors associated with the appearance of MDR strains include antibiotic abuse, therapeutic failures, and phenotypical mechanisms promoting resistance/tolerance of these bacteria to antimicrobial substances (efflux pumps expression, biofilm formation, or morphological transformation) [ 9 , 10 , 11 , 12 ]. High prevalence, carcinogenic potential, and ability of dynamic resistance spreading constituted the premise for including H. pylori in the list of twelve priority pathogens and the need to search for new methods eradicating this microorganism [ 13 ].…”
Section: Introductionmentioning
confidence: 99%